English Students' Perception toward the Use of Youtube in Improving Students' Pronounciation - Daulay, Ernita; Mu'adzah Rana, Nuha (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research aims to explore English students' views regarding the usage of social media platforms like YouTube, specifically the